The Role of Kindergarten in Developing Children’s Economic Concepts and Its Impact on Early Childhood Education - Aldossary, Norah Saleh Abdullah; Etman, Ali Abd Eltawab Mohamed; Omar, Sahar Mansour Sayed (Journal of Posthumanism, 2025)
This study aims to identify the role of kindergartens in developing economic concepts and their impact on early childhood education. The study used a descriptive-analytical approach and was conducted on a sample of 109 kindergarten teachers from kindergartens in Najran, Saudi Arabia. A questionnaire was used as a tool. The results indicated the importance of kindergartens in developing children’s economic concepts at this early stage in several key aspects. These include an educational unit for developing financial awareness among kindergarten children. Teachers provide opportunities for children to express their opinions and perspectives on the concept of spending. Large portions of kindergarten daily activities include developing financial awareness among kindergarten children. Teachers provide opportunities for children to think and be creative about the culture of thrift and savings. The kindergarten teacher takes into account individual differences among children in their understanding of the meaning of financial awareness. Overall, the evaluation was positive, reflecting the great interest that kindergartens in Najran place in developing economic concepts among kindergarten children.